Life cycle closure of Cerroneuroterus minutulus (Giraud, 1859) with C. aggregatus (Wachtl, 1880) (Hymenoptera: Cynipidae: Cynipini): experimental, taxonomic and molecular approaches - Sottile, Salvatore; Nicholls, James A.; Cerasa, Giuliano (Zootaxa, 2024)
The life cycle of Cerroneuroterus minutulus (Giraud, 1859), a species previously known only from its asexual generation, is closed. Our study demonstrates that C. minutulus exhibits the heterogony typical of Cynipini species, with alternating sexual and asexual generations. The identity of the sexual generation is demonstrated by laboratory experiments and confirmed by molecular data, with Cerroneuroterus aggregatus (Wachtl, 1880) determined to be the sexual generation, and junior synonym, of Cerroneuroterus minutulus (Giraud, 1859). Illustrations and diagnoses for adults and galls, observations on biology and distribution information are provided as is a detailed redescription of the sexual generation of C. minutulus.